2016
DOI: 10.1371/journal.pone.0146654
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aerobic Glycolysis Attenuates Disease Progression in Polycystic Kidney Disease

Abstract: Dysregulated signaling cascades alter energy metabolism and promote cell proliferation and cyst expansion in polycystic kidney disease (PKD). Here we tested whether metabolic reprogramming towards aerobic glycolysis (“Warburg effect”) plays a pathogenic role in male heterozygous Han:SPRD rats (Cy/+), a chronic progressive model of PKD. Using microarray analysis and qPCR, we found an upregulation of genes involved in glycolysis (Hk1, Hk2, Ldha) and a downregulation of genes involved in gluconeogenesis (G6pc, Lb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 38 publications
4
91
0
1
Order By: Relevance
“…Warburg effect accelerates cyst expansion in PKD. Riwanto et al () show that glycolytic shift occur in cyst epithelial cells from PKD. A significant increase in the transcript levels of aerobic glycolysis enzymes and a decrease in mitochondrial oxidation are caused in PKD, which forces the cyst epithelial cells to generate ATP by aerobic glycolysis pathway.…”
Section: Warburg Effect Accelerates Cyst Expansion In Pkdmentioning
confidence: 99%
“…Warburg effect accelerates cyst expansion in PKD. Riwanto et al () show that glycolytic shift occur in cyst epithelial cells from PKD. A significant increase in the transcript levels of aerobic glycolysis enzymes and a decrease in mitochondrial oxidation are caused in PKD, which forces the cyst epithelial cells to generate ATP by aerobic glycolysis pathway.…”
Section: Warburg Effect Accelerates Cyst Expansion In Pkdmentioning
confidence: 99%
“…At present, both drugs have been used alone or in combination for the treatment of cancer in Phase I and II clinical trials (Cheong et al, 2011), and an inhibitory effect on cancer cell proliferation has been reported. As polycystic kidney cells exhibit similar abnormalities as cancer cells in terms of glucose metabolism and proliferation, 2DG and metformin have been tested as monotherapies for the short-term treatment of PKD in rodents (Chiaravalli et al, 2016;Riwanto et al, 2016). However, no study has investigated the possibility of using a combination of these two agents for the long-term treatment of PKD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that either direct inhibition of mTOR signalling using rapamycin or indirect inhibition using the AMPK agonist metformin can reverse the glycolytic phenotype of ADPKD cells in vitro (Riwanto et al, 2016). AMPK is a crucial molecule in the regulation of energy metabolism (Hardie, 2008;Rehman et al, 2014).…”
mentioning
confidence: 99%
“…In recent years, there has been increasing evidence demonstrating the utility of investigating these parallels such that available cancer drugs can be repurposed to treat ADPKD 46 . It should not be surprising that these drugs work in light of the fact that there are many metabolic pathways shared between cancer and cystic disease which have been associated with epithelial proliferation, cell death pathways, and consequent cyst formation in ADPKD.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a great deal known about the signaling defects underlying this disease, an enormous effort to evaluate targetable pathways, and new discoveries frequently added, there are still no ADPKD specific therapies currently available. Efforts in our 4 and other 5,6 laboratories have focused on metabolic reprogramming in PKD which in many cases shows a striking similarity to malignancy. Through conventional principles that drive oncologic research, studies on cyst formation in PKD can lead to re-purposing of effective cancer drugs for use in these patients.…”
Section: Introductionmentioning
confidence: 99%